The role of microRNAs in acrylamide toxicity - Homayoonfal, Mina; Molavizadeh, Danial; Sadeghi, Sara; Chaleshtori, Reza Sharafati (Frontiers in Nutrition, 2024)
The chemical compound known as Acrylamide (AA) is employed in different industries worldwide and is also found in thermal-processed food. AA has been acting as a reproductive toxicant, carcinogen, and neurotoxic in various animals, which may promote several toxic impacts in animal and human species. Up to now, various studies have focused on the harmful mechanisms and intervention actions of AA. However, the underlying mechanisms that AA and its toxic effects can exert have remained uncertain. MicroRNAs (miRNAs) are a class of short, non-coding RNAs that are able to act as epigenetic regulators. These molecules can regulate a wide range of cellular and molecular processes. In this regard, it has been shown that different chemical agents can dysregulate miRNAs. To determine the possible AA targets along with mechanisms of its toxicity, it is helpful to study the alteration in the profiles of miRNA regulation following AA intake. The current research aimed to evaluate the miRNAs' mediatory roles upon the AA's toxic potentials. This review study discussed the AA, which is made within the food matrix, the way it is consumed, and the potential impacts of AA on miRNAs and its association with different cancer types and degenerative diseases. The findings of this review paper indicated that AA might be capable of altering miRNA signatures in different tissues and exerting its carcinogen effects.